An epidemiological study of dog bite cases in a rural area of Salem, Tamil Nadu - Sangeetha S.; Shakthi Shri Hari M.V.; Sarala Devi M.; R. Saravana Kumar; Sathana R.; M. Renasre; K. Shanadhani (Public Health Review: International Journal of Public Health Research, 2018)
Introduction: Rabies is a viral zoonosis. In up to 99% of cases, domestic dogs are responsible for rabies virus transmission to humans. About 30% of the victims of dog bites are children under the age of 15.Objective: To assess the epidemiological pattern of dog bite cases, which formed the majority of cases attending anti-rabies clinic.Materials and Methods: This study was conducted at the Primary Health Centre, Poolavari, Salem, Tamil Nadu, India between Feb 1st- May 1st2018.It is a cross sectional study, where all dog bite cases attending injection OPD were studied. A questionnaire-based survey was conducted amongst dog bite patients in the Primary Health Centre at Poolavari, Salem.Results: Highest percentage of dog bite victims belonged to the age group of 5-25Years(33.7%). The bites were mostly by pet dogs (75.5%). 91.8% of the dogs were not vaccinated. Running, patting were the most common factors leading to dog bites (50.0%). 52% of the study population had awareness of first aid for dog bite.88.8% population had awareness about Anti rabies vaccines for dog bites. Most of the victims took the treatment within ½ hr (30.6%). 81.6% of the victims took allopathy treatment.Conclusion: The study concludes that awareness of first aid for dog bites, pet dog vaccination, awareness about Anti rabies vaccine for dog bites and completion of the treatment should be increased in the rural population.